IKLIM ORGANISASI DAN SPIRITUALITAS KERJA DALAM MENINGKATKAN KINERJA KARYAWAN MELALUI KOMITMEN AFEKTIF PADA BMT AT-TAUBAH BANGIL - Riski Indryani, Meylinia; Rifdah Abadiyah (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the effect of Organizational Climate and Work Spirituality on Employee Performance with Affective Commitment as an intervening variable at BMT At-Taubah Bangil. This study uses a quantitative research type conducted at BMT At-Taubah Bangil. Data was collected by distributing questionnaires/questionnaires, with samples using saturated samples, where there were 60 respondents at BMT At-Taubah Bangil. The data analysis using the Outer model test includes the convergent validity test, discriminant validity and reliability and the Inner Model includes the R-square test. Hypothesis testing using Path Coefficient Test and Indirect Effect. The data management uses PLS software version 3.0. In this primary data collection is done by distributing questionnaires which are measured using an interval scale and secondary data collection through documents including company profiles, employee attendance, organizational structure, financial reports etc.